Some Fixed Point Theorems For Mappings Satisfying Contractive Conditions Of Integral Type - Jha , Naveen (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In this paper, we establish some common fixed-point theorems for two pairs of weakly compatible mappings satisfying integral type contractive conditions integral type in dislocated metric spaces by using E.A. which improves and extends similar known results in the literature. 2010 AMS Mathematics Subject Classification: 54H25, 47H10